Tofu Wastewater Treatment and Bioelectricity Production Potential by Combining Anaerobic Baffled Reactor and Microbial Fuel Cells - Nisa', Syadzadhiya Qothrunada Zakiyayasin; Murti, Restu Hikmah Ayu; Ni'am, Achmad C.; Sitogasa, Praditya Sigit Ardisty; Wibowo, Elysia C. (Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Anaerobic Baffled Reactor (ABR) systems have only been utilized to reduce pollutant compounds in wastewater. Anaerobic conditions in ABR can double as an anode chamber in Microbial Fuel Cells (MFCs) which require anaerobic conditions. This study aims to test the ability of COD and TSS removal in tofu wastewater and the potential electricity generated from a combination unit of ABR and MFCs. The experiment was conducted on a laboratory scale using a continuous system for 96 hours. ABR reactor was made consisting of 5 compartments, where the second compartment was installed anode for MFCs. The cathode chamber of the MFCs system was made separate from the ABR reactor and filled with electrolyte solution. The anode chamber in the ABR and the cathode chamber are connected by a salt bridge. Electrodes used in MFCs are zinc as anode and copper as cathode. The removal of pollutants in tofu wastewater reached 55.85% for COD and 88.68% for TSS. The electrical potential of MFCs increases along with the increase of organic matter removal in wastewater. The electric voltage generated reached 0.94 V and electric current 0.40 mA. The power density generated in this MFCs system reached 94 mW/m².